Search for squarks and gluinos using final states with jets and missing transverse momentum with the ATLAS detector in √s=7 TeV proton-proton collisions - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (Elsevier, 2011)
A search for squarks and gluinos in final states containing jets, missing transverse momentum and no electrons or muons is presented. The data were recorded by the ATLAS experiment in √s=7 TeV proton-proton collisions at the Large Hadron Collider. No excess above the Standard Model background expectation was observed in 35 pb-1 of analysed data. Gluino masses below 500 GeV are excluded at the 95% confidence level in simplified models containing only squarks of the first two generations, a gluino octet and a massless neutralino. The exclusion increases to 870 GeV for equal mass squarks and gluinos. In MSUGRA/CMSSM models with tanβ=3, A0=0 and μ>0, squarks and gluinos of equal mass are excluded below 775 GeV. These are the most stringent limits to date.